Investigation and analysis of clinical medical undergraduate learning behaviors under different teaching models - Lan, Yang-Zheng; Lin, Wen-Ting; Wu, Zheng; Chen, Wen-Jia; Guo, Dan; Liu, Shu-Hui; Liu, Jing (Frontiers in Education, 2025)
Medical education plays a critical role in preparing future doctors, responsible for the well-being and health of individual patients. Given its unique significance, understanding how to enhance the intrinsic motivation of clinical medical undergraduates for a 5-year program is a key research focus in China. Based on this purpose, the transformation of higher education in the major of clinical medicine has been conducted worldwide. To evaluate the attitude of clinical medical undergraduates on the transformation of education, this study investigates the impact of different teaching models on the learning attitudes of students at Shantou University Medical School, aiming to provide insights into effective educational strategies. Within the set-up of different teaching models, involving active-learning classes, English-medium instruction classes, and conventional clinical classes, we employed a comprehensive survey targeting undergraduates enrolled in three distinct teaching models. The survey explored multiple dimensions of learning behaviors, including classroom engagement, study time, and overall motivation. Results indicated that students participating in active learning classes exhibited superior classroom engagement and devoted more time to their studies than those in English-medium instruction classes and conventional clinical classes, while the difference between English-medium instruction classes and conventional clinical classes was not significant. These students reported a higher intrinsic motivation towards their learning experience, suitable to apply self-directed learning methods. In conclusion, this study underscores the importance of adopting diverse and adaptive teaching strategies to cater to the varied learning attitudes of clinical medical undergraduates, suggesting conducting self-evaluation or pre-evaluation of the students for adapting to different clinical teaching methods. Meanwhile, enhancing teacher guidance and support throughout the learning process is essential. By implementing different educational approaches, medical schools can effectively enhance student motivation and educational outcomes, contributing to the advancement of medical education.